Production and Purification of aflatoxin b1 from Local Isolate of Aspergillus flavus - Mohammed Abdullah Zayer; Rafid Abdalwahd; Essam Fadel al-jumaili (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background and Objective: Aflatoxins are cancerogenic compounds produced predominantly by certain strains of the Aspergillus genus. Food and feed contamination by aflatoxin (AF)B1 has adverse economic and health consequences. Unfortunately, these contaminants can never be completely removed, and on that account, many studies have been carried out to explore an effective process of their detoxification to a threshold level. Results: A thermostable enzyme purified from the boiled supernatant was designated as Horseradish aflatoxin-degrading enzyme (HADE). An overall 9.55-fold purification of HADE with a recovery of 39.92% and an activity of 3.85 × 103 U·mg−1 was obtained using chromatography on DEAE-Sepharose. peroxidase had an estimated molecular mass of 34 kDa and exhibited the highest activity at 25 °C and pH 7.0. peroxidase is the major protein involved in AFB1 detoxification. Conclusion: PTLC It is reliable as it is a good and reliable method for separating compounds and toxins. It is necessary to study the other compounds that the Aspergillus fungus secretes, as they are likely to cause harms more dangerous than aflatoxin B1.